Cholesterol-Containing Nuclease-Resistant siRNA Accumulates in Tumors in a Carrier-free Mode and Silences MDR1 Gene - Ivan V. Chernikov; Daniil V. Gladkikh; Mariya I. Meschaninova; Alya G. Ven'yaminova; Marina A. Zenkova; Valentin V. Vlassov; Elena L. Chernolovskaya (Elsevier, 2017)
Chemical modifications are an effective way to improve the therapeutic properties of small interfering RNAs (siRNAs), making them more resistant to degradation in serum and ensuring their delivery to target cells and tissues. Here, we studied the carrier-free biodistribution and biological activity of a nuclease-resistant anti-MDR1 cholesterol-siRNA conjugate in healthy and tumor-bearing severe combined immune deficiency (SCID) mice. The attachment of cholesterol to siRNA provided its efficient accumulation in the liver and in tumors, and reduced its retention in the kidneys after intravenous and intraperitoneal injection. The major part of cholesterol-siRNA after intramuscular and subcutaneous injections remained in the injection place. Confocal microscopy data demonstrated that cholesterol-siRNA spread deep in the tissue and was present in the cytoplasm of almost all the liver and tumor cells. The reduction of P-glycoprotein level in human KB-8-5 xenograft overexpressing the MDR1 gene by 60% was observed at days 5-6 after injection. Then, its initial level recovered by the eighth day. The data showed that, regardless of the mode of administration (intravenous, intraperitoneal, or peritumoral), cholesterol-siMDR efficiently reduced the P-glycoprotein level in tumors. The designed anti-MDR1 conjugate has potential as an adjuvant therapeutic for the reversal of multiple drug resistance of cancer cells. Keywords: cholesterol-containing siRNA, MDR1, 2'-O-methyl modification, tumor xenograft in SCID mice, multiple drug resistance, biodistribution of siRNA